SOCIOCODE AND SOCIAL INTEGRATION OF KNOWLEDGE ISSUE - Natalya I. Basina; Svetlana L. Popova (Advanced Engineering Research, 2012)
The heuristic potential of the ‘sociocode’ concept in the analysis of the social essence and histori cal typology is considered. The qualitative difference typology of the cultural oases provides the basis f or solving the problem of ethnocultural contradictions. The thesis on the incompatibility of sociocodes is regarded as a meani ngful principal for the comprehension of the current civilizational conflict prospects. The incompatibility of socio codes is cause d by different ways and rates of the new knowledge acquisition and utilization, and of the social process es renewal. The foundations for conceptualizing ‘knowledge society’ are revealed.